2000
DOI: 10.4049/jimmunol.164.1.248
|View full text |Cite
|
Sign up to set email alerts
|

Th2-Dependent B Cell Responses in the Absence of CD40-CD40 Ligand Interactions

Abstract: CD40 is thought to play a central role in T cell-dependent humoral responses through two distinct mechanisms. CD4+ T helper cells are activated via CD40-dependent Ag presentation in which CD80/CD86 provides costimulation through CD28. In addition, engagement of CD40 on B cells provides a direct pathway for activation of humoral responses. We used a model of adenovirus-mediated gene transfer of β-galactosidase (lacZ) into murine lung to evaluate the specific CD40-dependent pathways required for humoral immunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
1
11
1
Order By: Relevance
“…Our finding that CD40 expression on B cells is necessary for B cell responses runs counter to a recent study (35) in which use of an agonistic Ab to CD28 was able to restore a Th2-dependent B cell response to an adenovirus vector in CD40L KO mice. The authors of this study concluded that direct CD40 signaling to B cells during a Th2-TD response is not required if Th cell function is activated.…”
Section: Discussioncontrasting
confidence: 99%
“…Our finding that CD40 expression on B cells is necessary for B cell responses runs counter to a recent study (35) in which use of an agonistic Ab to CD28 was able to restore a Th2-dependent B cell response to an adenovirus vector in CD40L KO mice. The authors of this study concluded that direct CD40 signaling to B cells during a Th2-TD response is not required if Th cell function is activated.…”
Section: Discussioncontrasting
confidence: 99%
“…In support of this hypothesis are previous reports of IgA synthesis in vertebrates by commensal bacteria in the absence of T cells, presumably through stimulation of B cells through toll-like receptors (14). Furthermore, serum IgA has also been observed in humans with CD40L deficiency and can be induced in CD40L -/-mice in the absence of CD40 stimulation (15,16). Taken together these observations suggest a CD40-independent mechanism for serum IgA in some patients with XHM-ED.…”
Section: Discussionsupporting
confidence: 74%
“…On the other, the transfer of B1 cells without T cells to SCID mice failed to produce significant gut IgA, arguing in favor of T cell involvement (7,12,14). Such involvement may, however, not require cognate T-B cell interactions but may still depend on CD40L expression or other factors surface expressed or released by activated T cells (15,16). Another site of potential interest for IgA B cell development is the large number of isolated lymphoid follicles (ILF) that are scattered along the antimesenteric border of the small intestine (8,17).…”
mentioning
confidence: 95%